The Role of The Teacher as A Facilitator in Project-Based Learning With AI Support - Yuna, Jung; Minho, Kim; Jiwon, Han; Jiwon, Lee; Suyitno, Suyitno (Al-Hijr: Journal of Adulearn World, 2025)
Project-based learning (PBL) has gained widespread recognition as an effective instructional method that promotes critical thinking, collaboration, and problem-solving skills among students. In this context, the role of the teacher as a facilitator is crucial in guiding students through the learning process while encouraging autonomy and exploration. With the increasing integration of artificial intelligence (AI) in education, AI tools have become valuable resources to support both teachers and students in PBL environments. However, the specific role of teachers as facilitators in AI-supported PBL settings remains underexplored. This study aims to investigate the role of the teacher as a facilitator in project-based learning environments where AI tools are utilized to enhance the learning experience. A mixed-methods approach was employed, including surveys, interviews, and classroom observations involving 150 students and 20 teachers from schools implementing AI-supported PBL. The study assessed the impact of AI tools on teacher facilitation and student outcomes in terms of engagement, creativity, and problem-solving abilities. The results indicate that AI tools significantly supported teachers in managing and facilitating PBL, allowing for more personalized guidance and efficient task management. Students reported higher levels of engagement and improved collaboration, while teachers emphasized the increased ability to focus on individualized support. This study concludes that the teacher’s role as a facilitator is essential in leveraging AI tools to optimize project-based learning, enhancing both teaching practices and student outcomes.